Designing E-Commerce Applications for Learning Products in University - Suryani, Karmila; Widyastuti, Rini; Khairi, Ashabul; Nurul, Muhammad (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
E-commerce applications to sell various products produced by students in higher education can increase income-generating. However, a few universities still use e-commerce to sell student products, especially learning products. This research aims to produce an e-commerce application for web-based learning products in universities. The research method is development research with a research design using the waterfall model. The waterfall model procedure consists of analysis, design, coding, and testing. The system design uses Unified Modeling Language (UML) modeling such as context diagrams, class diagrams, use case diagrams, and activity diagrams. The system's coding uses the PHP programming language, Jquery, and the Boostrap Framework. The testing stage is through black-box analysis carried out by experts in the field of system design, with the results of testing each case being well-integrated and feasible to be applied. The result of the research is a web-based e-commerce application that sells learning products in universities.